Adaptação acústico-prosódica entre falantes - Cabarrão, V. (2018)
This paper presents a global analysis of entrainment in map-task dialogues in European Portuguese, including 48 dialogues, between 24 speakers. Our main goal is to analyze the acoustic-prosodic similarities between speaker pairs, namely if there are global entrainment cues displayed in the dialogues, if entrainment is manifested in distinct sets of features shared amongst the speakers, if entrainment depends on the gender and role of the speaker (giver or follower), and if speakers tend to entrain more with specific interlocutors regardless of the role. Results show that globally speakers tend to be more similar to their partners than to their own speech in the majority of the analyzed features, a strong evidence for entrainment. Moreover, almost all the pairs of speakers display cues of global entrainment, even though in different degrees (speakers entrain but in distinct features). Additionally, the role and gender effects tend to be less striking than the specific interlocutor effect. Our results support the fact that all prosodic parameters are monitored by the speakers in our corpus, contrarily to studies for other languages, which indicate that the main cues are energy related.